Review on optimal planning and operation of charging stations for electric vehicles - Arjun, M. S.; Mohan, N.; Satish, K. R.; Patil, Arunkumar; Somashekar, D. P. (Institute of Advanced Engineering and Science, 2025)
Several factors need to be taken into account while planning the locations of electric vehicle charging stations. The thoughtful design and arrangement of charging stations, as a crucial component of the infrastructure supporting electric vehicles, is essential for the advancement of these kinds of vehicles. However, a number of intricate aspects, including policy economics, charging demand, user comfort when charging, and traffic circumstances, influence the design and arrangement of charging stations. With the goal to uncover competing interests and opportunities for collaboration in the operation and development of charging infrastructure, this study intends to assist researchers and technology developers in investigating cutting-edge techniques from the viewpoint of each constituent. Additionally, only a strong electric vehicle charging station (EVCS) infrastructure may provide some of the answers to the most basic EV concerns, like EV cost and range. The literature claims that several sorts of techniques, objective functions, and constraints for issue formulation have been used by the scholars. In addition, sensitivity analysis, vehicle to grid strategy, integration of distributed generation, charging kinds, objective functions, restrictions, EV load modelling, uncertainty, and optimization methodologies are examined for the most recent research publications. Discussions occur as well regarding the effects of the EV load on the distribution network, the environment, and the economy.